NRF2 Inhibits Cardiomyocyte Pyroptosis Via Regulating CTRP1 in Sepsis-Induced Myocardial Injury. Issue 4 (14th April 2022) - Teng, Yan; Li, Ningjun; Wang, Yi; Sun, Shuling; Hou, Junxia; Chen, Yahui; Pan, Haiyan
Abstract : ABSTRACT: C1q/tumor necrosis factor-related protein 1 (CTRP1) has been demonstrated as a crucial regulator in myocardial injury (MI). The present study aims to evaluate the mechanism of CTRP1 in sepsis-induced MI. The septic mouse model was established via cecal ligation and puncture and the in vitro cell model was established via lipopolysaccharide treatment. The mouse survival rate within 96 h was recorded. Morphologic changes of cardiomyocytes were observed and cell viability and cardiac functions were detected. CTRP1 and nuclear factor erythroid 2-related factor (Nrf2) expressions, creatine troponin-T, and creatine phosphokinase isoenzyme levels, and expressions of pyroptotic markers were determined. The binding relationship between Nrf2 and the CTRP1 promotor was predicted and verified. Rescue experiments were designed to confirm the role of CTRP1. CTRP1 was poorly expressed in septic mice. CTRP1 overexpression inhibited cardiomyocyte pyroptosis and improved cardiac functions, MI, and survival rate in septic mice. Nrf2was decreased in cecal ligation and puncture -treated mice. Nrf2 overexpression promoted CTRP1 expression via binding to the CTRP1 promotor and suppressed cardiomyocyte pyroptosis. CTRP1 downregulation abolished the inhibitory effect of Nrf2 overexpression on cardiomyocyte pyroptosis. Overall, Nrf2 promoted CTRP1 expression via binding to the CTRP1 promotor to inhibit cardiomyocyte pyroptosis, thereby alleviating MI in septic mice.